2021
DOI: 10.3389/fmars.2021.697561
|View full text |Cite
|
Sign up to set email alerts
|

Microalgal Diet Influences the Nutritive Quality and Reproductive Investment of the Cyclopoid Copepod Paracyclopina nana

Abstract: Copepods represent an interesting alternative or a complement live food to brine shrimps and rotifers commonly used in aquaculture. They constitute the natural prey of many fish species and therefore do not require a potential nutritional enrichment. But an optimization of the microalgal diets used to feed copepods is essential to improve their mass culture. This study examined the effects of seven microalgal diets, namely single-species diets of Rhodomonas salina (R), Tisochrysis lutea (T), and Pavlova luther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 63 publications
(94 reference statements)
0
8
0
Order By: Relevance
“…sp.) was used to feed A. clausi as monoalgal diets do not meet the nutritional requirement of copepods namely Acartia sp (Zhang et al, 2013;Dayras et al, 2021). The suitability of these algae in terms of nutritive value for crustacean species has been previously confirmed (Støttrup and Jensen, 1990;Alvarez-González et al, 2001;Payne and Rippingale, 2001).…”
Section: Survival Rate Development Time and Sex-ratio In The F0 Gener...mentioning
confidence: 99%
“…sp.) was used to feed A. clausi as monoalgal diets do not meet the nutritional requirement of copepods namely Acartia sp (Zhang et al, 2013;Dayras et al, 2021). The suitability of these algae in terms of nutritive value for crustacean species has been previously confirmed (Støttrup and Jensen, 1990;Alvarez-González et al, 2001;Payne and Rippingale, 2001).…”
Section: Survival Rate Development Time and Sex-ratio In The F0 Gener...mentioning
confidence: 99%
“…Our data showed no difference in body size between O. nana that were fed single and mixed algae diets. This is not the case in other cyclopoids, such as Paracyclopina nana , which were found to have larger body sizes when fed mixed diets [ 91 ]. The body size range for each stage of O. nana recorded in this study corresponds to the sizes reported in natural and cultured conditions by other authors, indicated in Table 4 .…”
Section: Discussionmentioning
confidence: 98%
“…Our findings of beneficial impacts of including NSS microalgae mixture in Nile tilapia diets on deposition of DHA and EPA (two important omega-3 PUFAs) are also consistent with a previous observation [ 75 ], where higher PUFAs were observed with increasing the supplementation level of Schizochytrium species enriched with DHA fatty acid. Moreover, incorporation of microalgae enriched with DHA and EPA increased their contents in copepods [ 76 ]. Additionally, feeding of sea bream on diets enriched with microalgae blends including Nannochloropsis , oculata , and Schizocthytrium species displayed an increased long-chain n-3-PUFAs, DHA, and EPA levels [ 77 ].…”
Section: Discussionmentioning
confidence: 99%